2006
DOI: 10.1007/s00705-006-0891-z
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of the entire RNA genome of a sweet potato chlorotic fleck virus isolate reveals that it belongs to a distinct carlavirus species

Abstract: Since the paucity of information on sweet potato chlorotic fleck virus (SPCFV) had precluded its classification, we have determined the complete nucleotide sequence of the single-stranded RNA genome of a Ugandan isolate of SPCFV. The genome is 9104 nucleotides long (excluding the poly(A) tail) and potentially includes six open reading frames (ORFs). Based on genomic organisation and sequence similarity, SPCFV appears to be a member of the genus Carlavirus (family Flexiviridae). However, SPCFV is distantly rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…A single protein band of about 33 kDa was observed in SDS-PAGE. This size is similar to previous estimates (4,15) and falls within the range (31 to 36 kDa) obtained for other carlaviruses (1,2). During SPCFV purification, the CsCl gradients formed one major and a minor band above and below the virus band.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A single protein band of about 33 kDa was observed in SDS-PAGE. This size is similar to previous estimates (4,15) and falls within the range (31 to 36 kDa) obtained for other carlaviruses (1,2). During SPCFV purification, the CsCl gradients formed one major and a minor band above and below the virus band.…”
Section: Discussionsupporting
confidence: 90%
“…However, SPCFV remained unclassified until complete sequencing of a Ugandan isolate of SPCFV revealed that it has a singlestranded, positive-sense RNA genome consisting of 9,104 nucleotides (nt) containing six putative open reading frames (ORFs) and sharing highest nucleotide and amino acid sequence similarities with viruses of the genus Carlavirus in the family Flexiviridae (4). The closest relative of SPCFV is Melon yellowing-associated virus (MYaV), a whitely-transmitted carlavirus from Brazil (25), with which it shares ORF5 and ORF6 amino acid sequence similarities of 61 and 46%, respectively.…”
mentioning
confidence: 99%
“…no. AY461421) is 9104 nucleotides (nt) long, excluding the 3′-terminal poly(A) tail, and contains six open reading frames (ORFs) [67]. ORF5 encodes the coat protein (CP).…”
Section: Resultsmentioning
confidence: 99%
“…All three TGB sequences of MYaV formed a clade with SPCFV (Fig. 2), as did the CP sequence (as shown in Aritua et al 2007), and all trees exhibited a clear relationship between MYaV sequence and various carlavirus sequences. The amino acid sequences of MYaV and SPCFV shared 51% identity for TGBp1, 68% for TGBp2, and 30% for TGBp3.…”
mentioning
confidence: 73%
“…It is more closely related to SPCFV and Narcissus symptomless virus (NSV), both unassigned species but ones that will most likely be accepted as definite carlavirus members. Although the biological characterization of these two species are not well elucidated (Aritua et al 2007;Chen et al 2006), the clustering of TGB1p of MYaV, SPCFV, NSV and CPMMV suggests that they share a common biological feature, for instance, the vector type. The complete genome sequence of MYaV is essential to establish its taxonomic position, however, because of difficulties in virus maintenance in greenhouse conditions and the low virus concentration in infected plants, the remaining 5 0 end genomic region is still undetermined.…”
mentioning
confidence: 99%